Genomic Signature of the Standardized Uptake Value in (18)F-Fluorodeoxyglucose Positron Emission Tomography in Breast Cancer - Kim, Seon-Kyu (Cancers (Basel), 2020)
The standardized uptake value (SUV), an indicator of the degree of glucose uptake in (18)F-fluorodeoxyglucose positron emission tomography (FDG-PET), has been used for predicting the clinical behavior of malignant tumors. However, its characteristics have been insufficiently explored at the genomics level. Here, we aim to identify genomic signatures reflecting prognostic SUV characteristics in breast cancer (BRC). Through integrative genomic profiling of 3710 BRC patients, including 254 patients who underwent preoperative FDG-PET, we identified an SUV signature, which showed independent clinical utility for predicting BRC prognosis (hazard ratio [HR] 1.27, 95% confidence interval [CI] = 1.12 to 1.45, p = 2.23 × 10(−4)). The risk subgroups classified by the signature exhibited mutually exclusive mutation patterns of TP53 and PIK3CA and showed significantly different responsiveness to immunotherapy. Experimental assays revealed that a signaling axis defined by TP53–FOXM1 and its downstream effectors in glycolysis–gluconeogenesis, including LDHA, might be important mediators in the FDG-PET process. Our molecular characterizations support an understanding of glucose metabolism and poor prognosis in BRC with a high SUV, utilizable in clinical practice to assist other diagnostic tools.